PEMBAGIAN WARIS ANAK ANGKAT BERDASARKAN HUKUM WARIS ADAT - Islami, Sultan Satria; Lestari, Dewi Wahyu (Gapenas Publisher, 2023)
Customary law plays an important role in the development of the national legal system through laws and regulations. The Bugis tribe, as one of the four tribes in South Sulawesi, has a tradition of inheritance law that is rooted in the parental kinship system. One of the main aspects of customary law that contributes to the development of national inheritance law is customary inheritance law. The results of the study show that in the Bugis community, the distribution of heritage is carried out through three methods: grants, wills or last wills and wills, as well as after the heirs die